HUBUNGAN ANTARA MOTIVASI AWAL TENAGA PENJUAL DAN KINERJA PERUSAHAAN - Haryono, PM Budi (L2Dikti Wilayah III, 2017)
Motivation is an important factor for employee especially for salesman in doing his job productively and qualified. The objective of this research is to find out: (1) How far is the employee’s motivation in his job. (2) How far is the employees’ initial motivation which is already suitable with his interest. The methods used quantitive approch by collecting data with questionaires and interviews. The sampling taken purposively from 10 respondents who are the sales men of 17 sales forces of companis located in Jakarta. The results show that: (1) the employees’ motivation influences significantly to their performance in doing their job. (2) The initial motivation of the employee is needed to help him in doing his job which is suitable with his interest. It is recommended for the recruitment and hiring process to have the potencial candidate who have initial mativation in his job.